Feto-maternal outcomes in near miss events in obstetrics - Kamboj, Apoorva; Mandrelle, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Maternal near miss is defined by world health organization as a woman, who being close to death survives a complication occurring during pregnancy, delivery or upto 42 days after her end of pregnancy.It is a retrospective diagnosis. Evaluation of near miss maternal morbidity and mortality is a surveillance method to assess the quality of obstetric care and determinants of poor maternal outcome. It is an indicator of quality of obstetrical care. Aims and objectives for current study was to evaluate the cause of near miss maternal morbidity in our hospital which occurred either in admitted patients or were referred from elsewhere and to study the maternal and fetal outcomes in all near miss cases. Methods: A retrospective review of obstetrical records as well as prospective analysis was done at Christian medical college and hospital, a tertiary care teaching institute in North India and referral centre. The study was done for a period of one year from November 2018 to October 2019 retrospectively and for 6 months from November 2019 to April 2020 prospectively. The maternal near miss cases were taken as per WHO criteria. Results: The age ranged from 19 years to 49 years with maximum belonging to age group of 20-24 years. Maximum number of cases was primigravida and was in third trimester. The primary obstetric complication evaluated were hypertensive disorders followed by hematological diseases, viral hepatitis, haemorrhage, and obstructed labour or ruptured uterus. Conclusions: All the causes of MNM observed in this study are preventable causes, which can be identified timely and treated early to prevent maternal mortality, thereby, improving obstetrical and neonatal outcome.